PENERAPAN KEBIJAKAN RESENTRALISASI PERIZINAN ORGANISASI KEMASYARAKATAN DI KOTA DEPOK PROVINSI JAWA BARAT - Mohammad Rifa'i; Kurnia Fitria Pamungky (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2019)
Implementation of the Licensing Policy for Community Licensing in Depok City, West Java Province. This study aims to determine the extent of the application of policies on community organizations in the city of Depok. The Central Government takes a quick step by issuing Perppu Number: 2 of 2017 as a change to Law Number 17 of 2013 concerning Community Organizations. This policy is to anticipate the turmoil in the wider community, including what happened in Depok, so that with all the authority and tools available, the Government will immediately try to implement the Substitution Regulations for the Act. The method used is descriptive qualitative method with an inductive approach. The purpose of the use of the inductive approach is to explore the facts in the field related to the centralization of licensing organizations in the city of Depok and describe them systematically and factually to draw conclusions. In this study the authors used data sources from interviews as primary data. Meanwhile, the source of data from document tracking is secondary data. Thus, the data collection techniques used by the author are techniques: interview and documentation. The results show that the implementation of the Centralization Policy for Licensing Community Organizations in Depok City is not yet optimal. This can be seen from the performance and policy strategies of the Depok National Unity and Politics which still face obstacles related to the socialization, coordination and supervision of the registration of community organizations due to the existence of the decentralization policy. Keywords: policy; decentralization; community organization